2003
DOI: 10.1002/chin.200320136
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antiprotozoal and Anticancer Activity of Substituted 2‐Trifluoromethyl‐ and 2‐Pentafluoroethylbenzimidazoles.

Abstract: Benzimidazole derivativesBenzimidazole derivatives R 0200 Synthesis, Antiprotozoal and Anticancer Activity of Substituted 2-Trifluoromethyl-and 2-Pentafluoroethylbenzimidazoles. -The synthesis of some halogenated benzimidazoles is described. The antiprotozoal and anticancer activity of the newly synthesized and previously obtained benzimidazoles is studied. All benzimidazoles tested show remarkable antiprotozoal activity against Giardia intestinalis, Entamoeba histolytica and Trichomonas vaginalis. -(ANDRZEJEW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 1 publication
1
36
0
Order By: Relevance
“…This property allows for interaction with a variety of biomolecules, resulting in the diverse range of ascribed mechanisms of action, including reduction of fumarate, glucose uptake, and microtubule inhibition (30,31). Consistent with this notion, numerous biological functions have been described for this class of compounds, including antihelminthic, antifungal, antimicrobial, antiviral, and antineoplastic activity (32)(33)(34). Given the variety of these activities, previous studies have suggested that inhibition of cellular proliferation by mebendazole may involve effects in addition to its microtubule disruption properties.…”
Section: Discussionmentioning
confidence: 85%
“…This property allows for interaction with a variety of biomolecules, resulting in the diverse range of ascribed mechanisms of action, including reduction of fumarate, glucose uptake, and microtubule inhibition (30,31). Consistent with this notion, numerous biological functions have been described for this class of compounds, including antihelminthic, antifungal, antimicrobial, antiviral, and antineoplastic activity (32)(33)(34). Given the variety of these activities, previous studies have suggested that inhibition of cellular proliferation by mebendazole may involve effects in addition to its microtubule disruption properties.…”
Section: Discussionmentioning
confidence: 85%
“…Benzimidazoles containing carbamate-residue in position 2 and an H-atom in position 1, bind to tubulin and thereby inhibit its polymerization. A strong activity of halogenobenzimidazoles against Trichomonas vaginalis, Giardia intestinalis and Entamoeba histolytica (all of them have a tubulin cytoskeleton) was revealed in the earlier studies (Andrzejewska et al 2002.…”
Section: Discussionmentioning
confidence: 86%
“…3 Recently, potent anticancer, antibacterial, antifungal and antiprotozoal activities were reported for halogenated 2-trifluoromethyl-and 2-pentafluoroethyl-benzimidazoles. [4][5][6] Not only the substituted benzimidazole heterocycles themselves but also a series of modified benzimidazole nucleosides are biologically active. [7][8][9] Originally, their synthesis was encouraged by the discovery that 5,6-dimethyl-1-(α-D-erythro-pentofuranosyl)-benzimidazole is a constituent of vitamin B12.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,25,26 The introduction of side chains into position-2 of halogenated or non-halogenated benzimidazoles can be achieved by different routes. 5,6,[25][26][27] One route uses non-halogenated or halogenated o-phenylenediamines as precursor which give after condensation with carboxylic acids and their derivatives (nitriles, imidates, orthoesters) the 2-substituted benzimidazoles (Scheme 1). In this manuscript compounds of Figure 4 were prepared employing this protocol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation